Inflammatory Biomarkers Predicting Contrast-Induced Acute Kidney Injury in Elderly Patients with ST-Segment Elevation Myocardial Infarction - Suleyman Sezai Yildiz; Gokhan Cetinkal; Erkan Kalendar; Emre Daglioglu; Betul Balaban; Murat Avsar; Omer Sit; Mujdat Aktas; Kadriye Kilickesmez (Diagnostics)
Background: The inflammatory response is critically important in ST-segment elevation myocardial infarction (STEMI). The systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI), novel inflammatory biomarkers, have been linked to the determination of outcomes in various diseases. The aim of the current study was to examine the relation of the SII and SIRI with contrast-induced acute kidney injury (CI-AKI) in elderly subjects with STEMI undergoing primary percutaneous coronary intervention (pPCI). Methods: All patients diagnosed with STEMI between November 2020 and September 2024 were screened, and patients aged over 70 were retrospectively analyzed in the present study. The patients were divided into two groups according to CI-AKI development. The SII and SIRI were calculated based on the peripheral blood counts. A receiver operating characteristic (ROC) curve analysis was performed to determine the sensitivity and specificity of the SII and SIRI in predicting CI-AKI. Additionally, multivariable logistic regression models were employed to investigate the associations between inflammatory indices and the incidence of CI-AKI in elderly patients with STEMI. Results: A total of 263 participants were included (mean age 77.67 ± 6.20, 56% women). Both the SII and SIRI were higher in the CI-AKI group than in the non-CI-AKI group (3252 ± 2257, 1097 ± 991 p < 0.001 for SII; 12.1 ± 4.54, 4.86 ± 2.42 p < 0.006 for SIRI). In the receiver operating characteristic analysis, the SII and SIRI showed the highest area under curve (AUC) compared with other inflammatory parameters. The AUC of the SII and SIRI were 0.903 and 0.867 (p < 0.001). In multivariate logistic regression analysis, the SII and SIRI were found as independent predictors of CI-AKI. Conclusions: The SII and SIRI were found to be important markers for predicting post-procedural CI-AKI in elderly patients with STEMI.